A performance como ação midiática: os (não) limites entre arte e comunicação - Castanheira, Ludmila de Almeida (2011)
The objective of this master‟s dissertation is to analyze the narrower and narrower relation between the so-called performance art and the communicational phenomena. In some examples which are part of the corpus of this study such as the Apartment Festival and the series Estranho, um cara comum , from Flávio Rabelo the classic dichotomies between the artist and the public, object of art and daily fact appear more and more hybridized. Considering the nature often unclassifiable of these manifestations, their presence on the cultural journalism is practically inexistent, as well as in the edicts to stimulate art. In this way, another type of hybridization is identified, different from the classic definition of performance which identified it as an example of miscegenation among different artistic languages. The hypothesis of the study is that the performance crosses the areas of art and communication in such a way as to question the limits between these two areas of knowledge. For the theoretical grid authors such as Boaventura de Souza Santos (2008), Giorgio Agamben (2009), Katz e Greiner (2005; 2010), Schechner (1970), Cohen (2002; 2004) and Thompson (2008) were studied. The methodology is supported on the bibliographical research and on the analysis of the examples mentioned above. The expected result is a modest collaboration to the theoretical discussion which has been maturing since the 70s in countries such as the United States and Germany, but is still incipient among us Brazilians